Computer science studies in Vilnius University: Problems and perspectives - Brazaitienė, Tatjana; Brazaitis, Zenonas (Information & Media, 1997)
The development of Computer Science specialists’ preparation in Vilnius University between 1967-1996 is surveyed. The five programmes of the informatics specialities’ studies are analysed, and the orientation directions for specialists are defined. The object fields of computer science specialities are explained and the relations among them are estimated. The situation of the Computer Science specialists’ demand is analysed, taking into account their qualification and specialization. The necessity of work in collaboration is required not only among the faculties and departments, but among all the higher schools as well which prepare Computer Science specialists.